Comparison of Short Term Neurological Outcome in Patients of Hypoxic Ischemic Encephalopathy Treated with Erythropoietin Versus Intravenous Magnesium Sulphate - Meh Jabeen, Athar Razzaq, Muhammad Wasif Ijaz, Syed Hassan Ahmed, Fareeha Gul, Zahid Siddique Shad (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: Hypoxic-ischemic encephalopathy (HIE) in neonates remains a significant challenge in medical practice, requiring effective and reliable treatment options. Erythropoietin (EPO) and Intravenous Magnesium Sulphate (MgSO4) have been explored as potential therapies, but a direct comparison of their effectiveness has been lacking. Method: This study compared the effects of EPO and Intravenous MgSO4 in a sample of 38 neonates, evenly distributed between the two treatment groups. Parameters including maternal age, gestational age, neonatal age, weight, and several biochemical variables were assessed. Statistical analyses were conducted to reveal any significant differences between the two groups. Results: The evaluation across various parameters revealed no significant differences between the two treatments. All the tested variables, including primary outcomes such as HB levels, showed a similarity in the overall impact of Erythropoietin and Intravenous MgSO4, with p-values consistently above 0.05. Conclusion: The findings suggest that both Erythropoietin and Intravenous MgSO4 exhibit comparable effects in the treatment of neonates with HIE. The lack of significant differences prompts a need for further research to understand the nuanced differences and potential applications of each treatment method. These insights will be instrumental in guiding future therapeutic strategies for HIE. Keywords: Neonates, Hypoxic-Ischemic Encephalopathy, Erythropoietin, Intravenous Magnesium Sulphate, Treatment Comparison, Biochemical Variables.